Identifikasi Potensi Daerah Menggunakan Metode K-Means Clustering pada Pendaftaran Tanah Sistematis Lengkap - Deno Yulfa Ardian; Sarjon Defit; Yuhandri Yunus (Jurnal Informasi dan Teknologi, 2020)
The lack of public awareness in some regions in making land title certificates has resulted in the Program Pendaftaran Tanah Sistematis Lengkap (PTSL) being unable to run evenly. This study aims to identify areas that have the potential for making land certificates so that there is an equal distribution of the PTSL program. Based on PTSL data for 2017, 2018, and 2019 in the City of Bukittinggi, there are several urban villages that still have low potential in making certificates. The K-Means method can be used to group data from an area. The results of the testing of this method were 3 clusters of potential areas were obtained, so that the potential approach of land registration areas was obtained through the PTSL program to achieve the complete city target by the Bukittingi City Land Office.